2020
DOI: 10.3389/fnhum.2020.00349
|View full text |Cite
|
Sign up to set email alerts
|

Individual Baseline Performance and Electrode Montage Impact on the Effects of Anodal tDCS Over the Left Dorsolateral Prefrontal Cortex

Abstract: Anodal transcranial direct current stimulation (tDCS), applied over the left dorsolateral prefrontal cortex (lDLPFC), can produce significant effects on working memory (WM) performance and associated neurophysiological activity. However, results from previous studies are inconsistent and occasionally contradictory. This inconsistency may be attributed to methodological and individual differences during experiments. This study therefore investigated two hypotheses: (1) A multichannel-optimized montage was expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 81 publications
(111 reference statements)
1
18
0
Order By: Relevance
“…The choice of the statistical approach (i.e., comparison between baseline and post-tDCS performance vs. controlling for individual baseline performance) was the main factor influencing the results. Indeed, in line with the literature about the state-dependency of tDCS effects [ 9 , 57 , 59 ], studying the impact of the baseline level of performance highlights the variability of tDCS effects, both by “correcting” post-stimulation effects (thus preventing from “false positives”) and by showing under which circumstance tDCS is most effective (thus preventing from “false negatives” from group-averaged analysis).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The choice of the statistical approach (i.e., comparison between baseline and post-tDCS performance vs. controlling for individual baseline performance) was the main factor influencing the results. Indeed, in line with the literature about the state-dependency of tDCS effects [ 9 , 57 , 59 ], studying the impact of the baseline level of performance highlights the variability of tDCS effects, both by “correcting” post-stimulation effects (thus preventing from “false positives”) and by showing under which circumstance tDCS is most effective (thus preventing from “false negatives” from group-averaged analysis).…”
Section: Discussionmentioning
confidence: 57%
“…Indeed, when the baseline performance was considered to predict tDCS effects, no modulation of gaze position was found after tDCS. Several studies have previously shown the impact of the level of baseline performance and of the brain activation state on tDCS efficacy [ 9 , 57 , 59 ]. Here, we found a positive association between the baseline attentional bias (leftward or rightward) and post-tDCS performances, but regardless of the type of stimulation (real or sham) and of the target area (FEF, PPC), indicating overall stability of gaze position across stimulation sessions, as well as before and after tDCS.…”
Section: Experiments 1—conventional Tdcsmentioning
confidence: 99%
“…Each trial consisted of 500 ms picture presentation followed by fixation cross presentation jittered between 1600 and 2000 ms duration, resulting in a trial duration of 2100–2500 ms. This 2-back task was previously included in our study with healthy adults 24 and is based on the verbal WM n-back task 47 , 48 . At baseline measurement (T1) and at each stimulation visit (T2–T5) participants performed a short training (23 trials) to ensure the task was understood correctly.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative could be optimised multichannel montages, for which modelling studies predict a comparatively strong but also focal stimulation of the target area 21 , 22 . For adults, an increased effectiveness of an optimised multichannel montage has already been shown for motor cortex stimulation 23 as well as lDLPFC stimulation 24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation